Prognostic role of pre-treatment serum AFP-L3% in hepatocellular carcinoma: systematic review and meta-analysis. - Jiwen Cheng; Wanli Wang; Yingjun Zhang; Xi Liu; Muxing Li; Zheng Wu; Zhengwen Liu; Yi Lv; Bo Wang (PLoS ONE, 2014)
Background Serum lens culinaris agglutinin-reactive fraction of α-fetoprotein (AFP-L3%) has been widely used for HCC diagnosis and follow-up surveillance as tumor serologic marker. However, the prognostic value of high pre-treatment serum AFP-L3% in patients with hepatocellular carcinoma (HCC) remains controversial. We therefore conduct a meta-analysis to assess the relationship between high pre-treatment serum AFP-L3% and clinical outcome of HCC. Methods Eligible studies were identified through systematic literature searches. A meta-analysis of fifteen studies (4,465 patients) was carried out to evaluate the association between high pre-treatment serum AFP-L3% and overall survival (OS) and disease-free survival (DFS) in HCC patients. Sensitivity and subgroup analyses were also conducted in this meta-analysis. Results Our analysis results showed that high pre-treatment serum AFP-L3% implied poor OS (HR: 1.65, 95%CI: 1.45-1.89 p<0.00001) and DFS (HR: 1.80, 95% CI: 1.49-2.17 p<0.00001) of HCC. Subgroup analysis revealed that there was association between pre-treatment serum AFP-L3% and endpoint (OS and DFS) in low AFP concentration HCC patients (HR: 1.96, 95% CI: 1.24-3.10, p = 0.004; HR: 2.53, 95% CI: 1.09-5.89, p = 0.03, respectively). Conclusion The current evidence suggests that high pre-treatment serum AFP-L3% levels indicated a poor prognosis for patients with HCC and AFP-L3% may have significant prognostic value in HCC patients with low AFP concentration.